ANALISIS TITIK PULANG POKOK USAHA KACANG GOYANG PADA INDUSTRI PRIMA JAYA - Tantu, Akbar Ishak; Sulaeman, Sulaeman (AGROTEKBIS, 2017)
This study aimed to determine the total cost of production, physical production, sale price and revenue generated by Prima Jaya industry for its Kacang Goyang business in Palu in order to find the break even point of the business.The study location and its four respondents were purposively selected. Qualitative analysis was used to descriptively depictgeneral profile, cost and income of the business whereas quantitative analysis was employed to determine the break even point. The revenue of Prima Jaya industry was found to be IDR 42,000,000/month with production cost spent was IDR 31,298,261/month, therefore its income generated was 10,701,739/month. The break even point was achieved at 70 packs for the price of IDR 40,000/pack.Keywords:Break even point, Home industry,income, and Prima Jaya industry.